2007
DOI: 10.1016/j.vaccine.2007.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunogenicity of trivalent influenza vaccine administered by intradermal or intramuscular route in healthy adults

Abstract: The present study was undertaken with controls using equal doses ID and IM plus the standard full dose IM to assess the role of route of vaccine in immunogenicity of inactivated influenza vaccine. The study was a prospective, randomized, active-controlled, open label clinical trial conducted in healthy young adult outpatients to compare the effect of route (IM vs ID) on antibody responses to influenza vaccine. Volunteers received 3, 6 or 9 μg of vaccine by ID or IM route; 15 μg IM was also studied. Low doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 11 publications
4
76
0
Order By: Relevance
“…Minimal use of antigenic material is essential to ensure the widest possible availability of both seasonal and pandemic influenza vaccines when supplies are limited by high-demand and restraints in global manufacturing capacity. Consistent with previous studies, 24,26,29,32,37,42 ID vaccination was associated with an increased frequency of mild to moderate local reactions which accompanied the inflammatory process taking place in the skin. For example, injection site erythema was experienced by 92% of subjects in the ID groups compared with 22% and 34% in the IM non-adjuvanted and IM MF59-adjuvanted groups, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Minimal use of antigenic material is essential to ensure the widest possible availability of both seasonal and pandemic influenza vaccines when supplies are limited by high-demand and restraints in global manufacturing capacity. Consistent with previous studies, 24,26,29,32,37,42 ID vaccination was associated with an increased frequency of mild to moderate local reactions which accompanied the inflammatory process taking place in the skin. For example, injection site erythema was experienced by 92% of subjects in the ID groups compared with 22% and 34% in the IM non-adjuvanted and IM MF59-adjuvanted groups, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…21 ID delivery of influenza vaccine may be an alternative to conventional intramuscular (IM) injection because the skin is an important natural barrier and immune organ which contains large numbers of Langerhans cells and resident dermal dendritic cells which, as professional antigen-presenting cells, are able to take up antigens at the site of injection, migrate to the draining lymph nodes, and there trigger an effective immune response by activating antigen-specific T cells. 22,23 Although preliminary results of ID vaccination against influenza are promising and have demonstrated good immunogenicity with lower antigen doses compared with IM administration, [24][25][26][27] the traditional ID technique for vaccine delivery (the Mantoux technique) is not easy to perform correctly and requires trained personnel and fine maneuvering of a needle into a 1-2 mm deep layer of tissue. 28 To overcome these limitations, new ID injection devices have been developed to deliver vaccine more reliably and conveniently, which employ short needles (1.5 mm in length), 14,[29][30][31][32] and microneedles (<1.0 mm in length).…”
Section: Mf59mentioning
confidence: 99%
“…In these cases it is possible that a reduced dose delivered by the standard route would also have resulted in an equivalent immune response, as has been reported with some influenza vaccines. 26,27 Furthermore, the majority of dose-sparing trials have for reasons of practical simplicity delivered 10% or 20% of the standard dose intradermally. Finer dose-titrations such as those performed with influenza vaccines have shown that less-dramatic reductions in dose, such as a 40% reduction, might be more realistic.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Therefore, MF59 appears to enhance the immune response to antigens at a number of specific points. Many of these effects have not been reported for other approaches that have been developed for improving vaccine immunogenicity, including alternative adjuvants, virosomal antigen presentation 31 and intradermal vaccination 32 …”
Section: Mechanism Of Action Of Mf59mentioning
confidence: 99%